2015
DOI: 10.1111/hpb.12441
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic Cholangiocarcinoma: expert consensus statement

Abstract: An American Hepato-Pancreato-Biliary Association (AHPBA)-sponsored consensus meeting of expert panellists met on 15 January 2014 to review current evidence on the management of intrahepatic cholangiocarcinoma (ICC) in order to establish practice guidelines and to agree on consensus statements. The treatment of ICC requires a coordinated, multidisciplinary approach to optimize survival. Biopsy is not necessary if the surgeon suspects ICC and is planning curative resection, although biopsy should be obtained bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
362
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 411 publications
(372 citation statements)
references
References 77 publications
5
362
0
5
Order By: Relevance
“…The most frequent imaging patterns displayed by iCCA in the cirrhotic liver are a progressive homogeneous contrast uptake until the delayed (around 5ʹ) phase (MRI, CT) or an arterial peripheral-rim enhancement (CT) 198,199 . Currently, identifi cation of rare primitive liver cancers -such as HCC with stem cell features (CK19 + HCC), cholangiolocellular carcinoma and combined HCC-CCA -by imaging procedures is still a challenge 17,201 . After excluding HCC in cirrhosis, or in the context of a nodule in non-cirrhotic liver, biopsy is necessary 4,5 .…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequent imaging patterns displayed by iCCA in the cirrhotic liver are a progressive homogeneous contrast uptake until the delayed (around 5ʹ) phase (MRI, CT) or an arterial peripheral-rim enhancement (CT) 198,199 . Currently, identifi cation of rare primitive liver cancers -such as HCC with stem cell features (CK19 + HCC), cholangiolocellular carcinoma and combined HCC-CCA -by imaging procedures is still a challenge 17,201 . After excluding HCC in cirrhosis, or in the context of a nodule in non-cirrhotic liver, biopsy is necessary 4,5 .…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…On the other hand, photodynamic therapy can improve survival in patients with unresectable CCA [259][260][261] . The role of radiation therapy in CCA is still not clearly outlined, but radiation with concurrent chemotherapy has been recommended in margin-positive and node-positive iCCA and pCCA, and in unresectable pCCA ineligible for liver transplantation 201,217 . Thus, although results have been promising from the various locoregional types of therapy, conclusive evidence for efficacy in patients with CCA is still lacking and larger prospective randomized studies are warranted.…”
Section: Locoregional Therapymentioning
confidence: 99%
“…Surgical indication for ICC with multiple intrahepatic tumors remains controversial [9]. Several case series have shown that the presence of multiple tumors, found in up to 44% of the patients, is one of the strongest negative prognostic factors.…”
Section: Surgical Treatment For Iccmentioning
confidence: 99%
“…Metastases are a contraindication for surgery [109] . Recurrence free survival (RFS) rates at 3 and 5 years after surgery are 6-47 and 2-39%, respectively [105,106,110] , and the median [80] CREB5 [95] RFS is 14 months [105] .…”
Section: Treatment For Local Diseasementioning
confidence: 99%
“…Radiotherapy may also have a role in treatment of large tumors [105] . Consensus statements recommend the use of AT in high risk cases (R1 and N1 disease) [109] . Resection of local intrahepatic recurrence has only been shown to provide a modest survival benefit [102] .…”
Section: Treatment For Local Diseasementioning
confidence: 99%